US Emergency Department Visits for Adverse Drug Events From Antibiotics in Children, 2011–2015. (23rd August 2018) - Lovegrove, Maribeth C; Geller, Andrew I; Fleming-Dutra, Katherine E; Shehab, Nadine; Sapiano, Mathew R P; Budnitz, Daniel S
Abstract: Background: Antibiotics are among the most commonly prescribed medications for children; however, at least one-third of pediatric antibiotic prescriptions are unnecessary. National data on short-term antibiotic-related harms could inform efforts to reduce overprescribing and to supplement interventions that focus on the long-term benefits of reducing antibiotic resistance. Methods: Frequencies and rates of emergency department (ED) visits for antibiotic adverse drug events (ADEs) in children were estimated using adverse event data from the National Electronic Injury Surveillance System–Cooperative Adverse Drug Event Surveillance project and retail pharmacy dispensing data from QuintilesIMS (2011–2015). Results: On the basis of 6542 surveillance cases, an estimated 69464 ED visits (95% confidence interval, 53488–85441) were made annually for antibiotic ADEs among children aged ≤19 years from 2011 to 2015, which accounts for 46.2% of ED visits for ADEs that results from systemic medication. Two-fifths (40.7%) of ED visits for antibiotic ADEs involved a child aged ≤2 years, and 86.1% involved an allergic reaction. Amoxicillin was the most commonly implicated antibiotic among children aged ≤9 years. When we accounted for dispensed prescriptions, the rates of ED visits for antibiotic ADEs declined with increasing age for all antibiotics except sulfamethoxazole-trimethoprim. Amoxicillin had the highest rate of ED visits for antibiotic ADEs among children aged ≤2 years, whereas sulfamethoxazole-trimethoprim resulted in the highest rate among children aged 10 to 19 years (29.9 and 24.2 ED visits per 10000 dispensed prescriptions, respectively). Conclusions: Antibiotic ADEs lead to many ED visits, particularly among young children. Communicating the risks of antibiotic ADEs could help reduce unnecessary prescribing. Prevention efforts could target pediatric patients who are at the greatest risk of harm. Abstract : Nearly 70000 estimated pediatric emergency department (ED) visits are made annually for an antibiotic adverse drug event (ADE). Young children had the highest numbers and rates of ED visits for an antibiotic ADE. Interventions could be targeted to the pediatric patients who are at the greatest risk of ADEs.